Pengaruh Struktur Kepemilikan dan Manajemen Risiko atas Keputusan Investasi - Saptana Saptana; HM Thamrin; David A. Lasse (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of research to determine the effect of ownership structure and risk management on Investment Decision of sea transport companies listed on Indonesia Stock Exchange period 2014-2018. The research used quantitative method. The sample are financial report of 13 companies with 5-year observation period taken by purposive sampling technique. Data analysis used descriptive statistics and inferential path analysis. The result of the research shows: there is no dirrect effect of ownership structure on investment decision, there is no dirrect effect of risk management on investment decision, there is positive dirrect effect of ownership structure on risk management, and there is no indirrect effect of ownership structure on investment decision mediated by risk management.The conclusions of the study: there is a positive significant of ownership structure on risk management, so that the risk management improved by increased ownership structure.